Photosynthetic responses to light levels in drought-tolerant novel peanut (Arachis hypogaea L) genotypes - Rajanna G. Adireddy; Saseendran S. Anapalli; Manisha Ojha; Naveen Puppala; Krishna N. Reddy (Scientific Reports)
Abstract Drought is a significant abiotic stressor that reduces peanut production because it alters photosynthetic activity and impacts crop growth. Therefore, developing drought-tolerant peanut genotypes capable of maintaining higher photosynthetic rates (A) under stress is crucial. This study assessed changes in photosynthetic and chlorophyll fluorescence responses to light (photosynthetic photon flux density, PPFD) in newly bred drought-tolerant peanut genotypes. Ten genotypes [NM-3, NM-5, NM-6, NM-23, NM-69, NM-70, NM-74, NM-77, V-C, and C-76–16] were evaluated under full irrigation (FC100) and deficit irrigation (FC50) in a split-plot design with four replications in a greenhouse. Under high PPFD levels, genotype NM-5 with deficit irrigation exhibited significantly higher A, stomatal conductance (gs), quantum efficiency of photosystem II (ΦPSII), and electron transport rate (ETR) by 40–59%, 135–525%, 31–212%, and 31–102%, respectively, than check varieties (V-C and C-76–16) and other genotypes. The NM-74 and NM-77 genotypes also performed well under deficit irrigations but with slightly lower A, gs, ΦPSII, and ETR. Genotypes NM-5, NM-23, NM-74, and NM-77 exhibited significantly higher quantum efficiency of photosystem II (Fv’/Fm’) and photochemical quenching (qP) with higher light intensities in the daily cycle under deficit irrigation. The decline in ETR at the same PPFD levels in NM-3, NM 69, NM-70, and C-76–16 indicated photoinhibition or saturation of the photosynthetic apparatus compared to other genotypes. Concurrently, FC100 irrigation level minimizes photoinhibition, enhancing A, gs, ΦPSII, and ETR in the genotypes than FC50. Therefore, we conclude that NM-5, NM-74, and NM-77 genotypes can perform better under water deficit environments. As such, chlorophyll fluorescence parameters Fv’/Fm’ and qP can be considered for selective breeding to enhance photosynthetic efficiencies.